2005
DOI: 10.1007/s00497-005-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified endogenous ethylene production on sex expression, bisexual flower development and fruit production in melon (Cucumis melo L.)

Abstract: Members of the Cucurbitaceae family display a range of sexual phenotypes including various combinations of male, female, or bisexual flowers. Ethylene appears to be a key hormone regulating the sex determination process. Application of ethylene, or inhibition of ethylene action, increases or decreases the number of pistil-bearing buds, respectively. Elevated levels of ethylene production and expression of genes for ethylene biosynthesis, have been correlated with pistillate flower production. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…Our Wndings were consistent with the reports that increased endogenous ethylene production enhanced femaleness in transgenic melon (Cucumis melo L.), indicated by studies with 35S promoter driven ACS genes (Papadopoulou et al 2005) and a CRC promoter driven dominant negative etr1 gene (Little et al 2007). Papadopoulou et al (2005) and Little et al (2007) indicated ethylene eVects on carpel development in transgenic melon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our Wndings were consistent with the reports that increased endogenous ethylene production enhanced femaleness in transgenic melon (Cucumis melo L.), indicated by studies with 35S promoter driven ACS genes (Papadopoulou et al 2005) and a CRC promoter driven dominant negative etr1 gene (Little et al 2007). Papadopoulou et al (2005) and Little et al (2007) indicated ethylene eVects on carpel development in transgenic melon.…”
Section: Discussionsupporting
confidence: 92%
“…Papadopoulou et al (2005) and Little et al (2007) indicated ethylene eVects on carpel development in transgenic melon. However, we found no eVects of increased ethylene production on carpel development in transgenic P AP3 : CsACO2 Arabidopsis.…”
Section: Discussionmentioning
confidence: 98%
“…Growth regulators or phytohormones, especially ethylene / ethrel (Papadopoulou et al 2005, Manzano et al 2008 and gibberellic acid, i.e.GA 3 (Thomas 2008), are mostly used to modify sex expression in melon.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have shown that phytohormones are involved in changes of flower type, number and ratio of flowers of different sex types, modifications of flowering time and of other traits related to sex expression (Noguera et al 2005, Papadopoulou et al 2005, Stankovic et al 2005, Yamasaki et al 2005, Little et al 2007, Boualem et al 2008, Ouzounidou et al 2008, Martin et al 2009). Most of these studies were performed in cucumber, the model plant for studying sex expression in Cucurbitaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Significance of endogenous ethylene production for pistillate flower development has been demonstrated in melon by Papadopoulou et al (2005). 146 Constitutive overexpression of ethylene biosynthetic gene, ACS resulted in enhanced endogenous ethylene accelerating bisexual flower initiation, development of mature bisexual flowers and fruit set in melon.…”
mentioning
confidence: 99%